Process and Correlation Between Ecosystem Services Value and Ecological Risk in River Basin - Jiang Weifeng; Xu Yan; Li Donghua; Bi Shanshan; Li Qian; Lu Lin (Shuitu baochi tongbao)
[Objective] The spatio-temporal pattern and interrelationship between the value of ecosystem services and ecological risks in river basins were analyzed in order to ensure healthy and sustainable development of ecosystems, maintain regional ecosystem balance, and promote the coordinated development of human-land relationships. The results will provide a scientific reference for policy formulation for the comprehensive management of the Huaihe River basin. [Methods] Based on land use data and socio-economic statistical data for the Huaihe River basin in Anhui Province from 2000 to 2019, a dynamic evaluation model of ecosystem service value was established by using the dynamic equivalence method. The ecosystem service value of the study area was calculated for each year. Combined with spatial exploratory data analysis, the heterogeneity and correlation of the spatial and temporal evolution processes of the ecosystem service value (ESV) and ecological risk (ER) were discussed. [Results] ①Conversion of land types in the research area from 2000 to 2019 occurred frequently, with the greatest transfers occurring for construction land and farmland (1 488, 1 763 km2, respectively). ② The total amount of ESV exhibited a fluctuating upward trend, from 3.13×1010 yuan to 3.58×1010 yuan. The ecosystem services were mainly regulatory services. Farmland and water contributed more than 70% to the total ESV. The high value ESV area was located mainly in Liu'an City and on both sides of the Huaihe River tributaries. ③ The ER index was stable overall. The average fluctuation of ER in the study area was within the range of 0.01. The spatial distribution showed the characteristics of high in the central part of the region and low in the southwest. The high value ER area was mainly located around urban construction land. [Conclusion] The total number of ESVs in the study area exhibited a dynamic upward trend. ESV and ER exhibited spatial aggregation in the study area, and there were positive spatial association characteristics.